Primaryb realignment of Traumatic posterior urethral rupture. - Hussein, Malath A. (AL-Kindy College Medical Journal, 2011)
Background: Posterior urethral rupture remains one of the most difficult and controversial injuries to treat and its management still controversial. Aim: To assess the effect of primary realignment of posterior urethral rupture. Methods: in this study, 20 patients (mean age 24.7 years, range 12 to 39 years) were admitted to al-kindey teaching hospital, Baghdad, Iraq, with complete posterior urethral rupture associated with fractured pelvis following trauma (3 cases of fall from high, 17 cases of road traffic accidents). All the patients were operated upon at the day of accident to establish the alignment of the posterior urethra on a Foley’s catheter with bladder drainage by suprapubic catheter. Patients were evaluated post-operatively for urinary incontinence, erectile dysfunction, and urethral stricture. They were followed up for a mean period of 17 months (range, 10 to 20 months). Results: posterior urethral rupture was associated with pelvic fractures in 18 of 20 patients (90%), and only one case had bladder rupture (5%). Seven patients (35%) had evidence of post operative stricture. Erectile dysfunction was reported by 2 patients (10%). none of the patients had urinary incontinence. Conclusion: Primary realignment of PUR is a simple procedure associated with low morbidity. It is recommended for patients who are stable and have no other significant intra-abdominal and pelvic organ injuries.